2021
DOI: 10.1103/physrevb.104.014108
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced 1T to 3R structural phase transition in metallic VSe2 : X-ray diffraction and first-principles theo

Abstract: We study pressure-induced structural evolution of vanadium diselenide (VSe 2 ), a 1T polymorphic member of the transition metal dichalcogenide (TMD) family, using synchrotron-based powder x-ray diffraction (XRD) and first-principles density functional theory (DFT). Our XRD results reveal anomalies at P ∼ 4 GPa in the c/a ratio, V-Se bond length, and Se-V-Se bond angle, signaling an isostructural transition. This transition is followed by a first-order structural transition from the 1T (space group P 3m1) phase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…In a previous study, the starting SbI 3 samples were purchased from the Alfa Company without further purification, which were ground into fine powders to minimize the effects of preferred orientation and loaded into a diamond anvil cell. The similar discrepancy phenomena in high-pressure synchrotron XRD results caused by the divergence of starting samples, such as VSe 2 , HfS 2 , HfTe 3 , etc ., were also observed in other previously reported two-dimensional layered compounds; 38,40,41 (iii) the inconsistent XRD profiles beyond ∼8.0 GPa corresponding to different high-pressure structural phases of SbI 3 . In our present study, the asymmetrically broad (113) predominant peak and the emergence and disappearance of several feeble peaks in the synchrotron XRD pattern revealed an IPT within the pressure range of 8.0 GPa and 20.0 GPa, which still retained the initial high-pressure rhombohedral ( R 3̄) structural phase of SbI 3 .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In a previous study, the starting SbI 3 samples were purchased from the Alfa Company without further purification, which were ground into fine powders to minimize the effects of preferred orientation and loaded into a diamond anvil cell. The similar discrepancy phenomena in high-pressure synchrotron XRD results caused by the divergence of starting samples, such as VSe 2 , HfS 2 , HfTe 3 , etc ., were also observed in other previously reported two-dimensional layered compounds; 38,40,41 (iii) the inconsistent XRD profiles beyond ∼8.0 GPa corresponding to different high-pressure structural phases of SbI 3 . In our present study, the asymmetrically broad (113) predominant peak and the emergence and disappearance of several feeble peaks in the synchrotron XRD pattern revealed an IPT within the pressure range of 8.0 GPa and 20.0 GPa, which still retained the initial high-pressure rhombohedral ( R 3̄) structural phase of SbI 3 .…”
Section: Resultssupporting
confidence: 79%
“…are characterized by the striking inflection point in the lattice constant ratio. 22,35–39 Therefore, the first and second phase transitions of SbI 3 possibly belong to the IPTs resulting from the prominent compression of the c -axis and Sb–I bond under high pressure, while the third phase transition presumably originates from the R 3̄-to- C 2/ m structural transition. Moreover, the crystalline structures and the detailed atomic positions of SbI 3 at four characteristic pressures of 0, 3.0, 10.0 and 35.0 GPa are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10 As a consequence, the high-pressure structural transitions of CrBr 3 at the respective pressures of ∼10 and ∼17 GPa presumably belong to the second-order phase transformations, as previously reported in other binary compounds of Bi 2 S 3 , Sb 2 S 3 , Sb 2 Se 3 and VSe 2 . 21,39–42 Generally speaking, the transition pressures of CrBr 3 obtained from high-pressure experimental and theoretical calculation results would show a feeble divergence, which is possibly related to the subtle variation of free energy before and after the phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the physicochemical properties of VSe 2 have been tuned by several approaches, including intercalation, hybrid engineering, , as inclusion cathode battery materials, , that were demonstrated in a range of applications such as sensing, energy storage and conversion, field emission, spintronics, and catalysis processes. A high-pressure study of the bulk VSe 2 system has been recently reported . Despite the broad interest on this material, no report of studies of VSe 2 nanomaterials at high pressures is available.…”
Section: Introductionmentioning
confidence: 99%